Assessment of growth, floral and biochemical characteristics of wild rose (Rosa sp.) across varied elevations of Rawalakot, Azad Jammu and Kashmir - Inzamam-UL-Haq, Muhammad; Yaqoob, Abid; Zahid, Noosheen; Maqbool, Mehdi; Shehzad, Muhammad; Rahim, Nasir (Journal of Pure and Applied Agriculture, 2024)
Roses have held their status as exquisite decorative plants since ancient times, captivating people with their timeless beauty. The rising demand for roses as an industrial raw material has led to a significant increase in their value. The picturesque state of Azad Jammu and Kashmir is home to flourishing large-scale rose plantations, particularly in the stunning wilderness of Rawalakot, located in District Poonch. The objective of this study was to collect wild roses from four distinct locations, each characterized by a unique elevation, and to evaluate their growth, floral, and biochemical characteristics. These locations include Khai Gala at 6329 ft, Chota Gala at 5744 ft, Mutyal Mehra at 5341 ft and Drake at an elevation of 3378 ft. The comparative analysis of the roses revealed that those cultivated at higher elevations exhibited a remarkable increase in growth characteristics and petal diameter, with measurements indicating a substantial difference from their counterparts grown at lower elevations. Furthermore, the analysis of rosehip content demonstrated a significantly higher concentration of essential nutrients (such as total soluble solids: 40%; vitamin C 49.8 mg/100 g FW; total flavonoids 1.73 mg/100 g FW) in the rosehips of the higher-altitude roses, making them a more nutritionally dense source. The findings from the study demonstrate that the specific environmental conditions and variations in elevation significantly influence the physical characteristics and biochemical composition of wild roses. This suggests that there are opportunities to enhance the quality of roses through the implementation of tailored cultivation methods designed to accommodate the diverse elevations at which they grow.